Α-Synuclein-induced internalization of NMDA receptors in hippocampal neurons is associated with reduced inward current and Ca2+ influx upon NMDA stimulation. (6th August 2015) - Chen, Y.; Yang, W.; Li, X.; Li, X.; Yang, H.; Xu, Z.; Yu, S.
Highlights: α-Syn promotes internalization of the NMDA receptor in hippocampal neurons. Rab5B is required for α-syn-induced internalization of the NMDA receptor. α-Syn reduces NMDA receptor-mediated Ca 2+ influx. α-Syn decreases NMDA-elicited inward currents. Abstract: Abnormal α-synuclein (α-syn) expression and aggregation have been implicated in the pathogenesis of Parkinson's disease (PD), dementia with Lewy bodies (DLB), and Alzheimer's disease (AD). These neurodegenerative disorders, collectively known as synucleinopathies, are usually associated with cognitive impairment that could be caused by impaired hippocampal function. Although abnormal expressions of α-syn and N-methyl-d -aspartate (NMDA) receptor are frequently observed in the hippocampus of patients with synucleinopathies, how these proteins interact with each other in hippocampal neurons remains poorly understood. In the present study, primary cultures of hippocampal neurons and α-syn transgenic mice were used to investigate the effect of α-syn on NMDA receptors. Neurons were treated either by direct addition of recombinant human α-syn (hα-syn) to the medium, or by infection with the hα-syn gene, to increase intracellular levels of α-syn. In both cases, NMDA receptor NR1 subunits on the cell surface were reduced while the total amount of NR1 was unchanged, indicating an internalization of NR1 subunits. Neurons with elevated α-syn also showed a profound increase in Rab5B, an isoform of the small GTPases essential for NMDA receptor endocytosis. Knockdown of Rab5B expression by siRNA inhibited the α-syn-induced reduction in surface NR1. The in vitro findings were confirmed in α-syn transgenic mice, showing that increased α-syn expression was accompanied by reduced levels of surface NR1 and increased expression of Rab5B. Due to the essential role of NR1 subunits for assembling a complete NMDA receptor, its reduction on the cell surface indicated impaired receptor function. This was demonstrated by observations that neurons with elevated α-syn showed profound reductions in NMDA-elicited Ca 2+ influx and inward current, which were also inhibited by knockdown of Rab5B expression. Our data suggest that increased α-syn expression may impair NMDA receptor function in the hippocampus by reducing the density of NR1 subunits on the cell surface.